The supply and quality of STEM teachers - Tuan D. Nguyen (Humanities & Social Sciences Communications)
Abstract The future of the STEM workforce rests partly on the strength of the STEM teacher workforce to teach and nurture new generations of STEM graduates. However, the STEM teacher workforce is facing critical decline with the annual production dropping from about 31,000 a decade ago to around 20,000 in the last few years. This is concerning given the need for more STEM teachers to meet rising demands. Although production is decreasing, there are improvements in the diversity and qualifications of STEM teachers, including more female teachers and those with higher degrees in STEM fields. Investments in teacher salaries and financial support for STEM education can help address the shortage and improve the future STEM teacher workforce and STEM workforce.